Pyridine on Colloidal Silver. Polarization of Surface Studied by Surface-Enhanced Raman Scattering and Density Functional Theory Methods - Kaczor, Agnieszka; Malek, Kamilla; Baranska, Malgorzata (Journal of physical chemistry. C, 2010)
Surface-enhanced Raman scattering (SERS) spectra of pyridine in various Ag colloids with different excitation wavelengths (514.5 and 1064 nm) were recorded and compared with the theoretical models computed with application of the static density functional theory method in order to simulate the chemical enhancement. Pyridine was chosen as a model compound to look at the surface enhancement since it is a well-known and extensively studied molecule by using SERS spectroscopy, and hence of great significance to the subject. Moreover, it was the first species for which a SERS spectrum obtained on electrochemically roughened silver surface was reported. The arrangement of pyridine on metal particles in the solution allows neglecting the solvent effects and placing the focus only on the interaction between adsorbent and metal surface to study the SERS mechanism. The intensity of bands in the fingerprint region of pyridine SERS spectra depends not only on the excitation wavelength but also on the applied colloid and the way in which it is activated or the potential of the electrode if such methodology is applied. With the help of theoretical calculations using various models of pyridine in the presence of silver nanoparticles, several parameters are predicted (e.g., the charge of the pyridine nitrogen, N−Agadatom distance). Good reproducibility of relative intensities of the Raman bands in the SERS spectra was achieved with the application of theoretical models and related to the polarization of the metal surface. The polarization of the surface, experimentally induced by increase of the negative potential of the electrode or adding chloride ion to the colloid, was reproduced computationally by varying of the size of cluster models (using systems with 5, 9, and 25 Ag atoms) and including chloride ions in the computed models (with negative charge set on Cl in the nine-silver-atom model).